A critical appraisal of systematic reviews assessing the effect of chronic velocity-based resistance training on health and athletic performance outcomes: A systematic review - Andres F. Loaiza-Betancur; Cristian González-González; Alejandro Díaz-Franco; Jeferson Castaño-Soto; Alejandro Alzate-Toro; Elias Areiza-Usuga; Diego A. Zuluaga-M; Juan Osvaldo Jiménez-Trujillo; Andrés M. Echavarría‑Rodríguez; Víctor Díaz‑López; Iván Chulvi-Medrano; Lisette Ethel Iglesias-González (PLoS ONE, 2026)
Introduction Systematic reviews have become increasingly popular among researchers due to their importance in decision-making in health and sports. Only 3% of the reviews are considered decent and clinically useful, and 17% are decent but not useful. Therefore, we aimed to synthesize and critically appraise the evidence of systematic reviews assessing the effect of velocity-based resistance training (VB-RT) on health or athletic performance outcomes in adults and older adults. Methods We searched MEDLINE (via Ovid), EMBASE (via Elsevier), Cochrane Database of Systematic Reviews (CDSR) (via Ovid), SPORTDiscus (via EBSCO), and Epistemonikos from inception to January 09, 2024, and updated May 26, 2025, to identify reviews of randomized controlled trials and non-randomized controlled trials investigating the effects of VB-RT on health or athletic performance outcomes in adults and older adults. Two reviewers independently selected the studies, extracted data, and assessed the overall confidence in the results of the included reviews with AMSTAR-2 as ‘High’, ‘Moderate’, ‘Low’, and ‘Critically low’. Descriptive analysis was used to summarize the characteristics of the included systematic reviews. We investigated the degree of overlapping in the reviews. Results We included 17 reviews published between 2019 and 2025 in 10 countries, with 8222 participants. Most of the reviews (65%) investigated non-athlete adults. Only 4 (24%) used an formal system to evaluate the certainty of evidence. The degree of overlap in primary studies was moderate (CCA = 7.73%). The overall confidence in the results of 16 reviews (94%) was rated as ‘Critically low’, and only one (6%) was rated as ‘Low’. Conclusion Systematic reviews of VB-RT studies often have serious limitations. Authors can improve confidence in the results of future reviews by involving methodologists and statisticians and using a rigorous and transparent system to evaluate the certainty of the evidence. Reviewers should also adhere to the latest standards of conduct and reporting, fostering a more cohesive, precise, and reliable understanding of the VB-RT role in performance and health outcomes.